Ophthalmia nodosa and the oculoglandular syndrome of Parinaud. Issue 7 (July 1986) - Martin, X; Uffer, S; Gailloud, C
Abstract : We present a case of ophthalmia nodosa and Parinaud's oculoglandular syndrome in a patient scratched by a cat six and a half months previously and who gave a positive result to an antigen test for cat scratch disease. In conjunctival swabs were also found urticarial hairs, tracheal fragments, processionary caterpillar oenocytes, and a grain of pollen. The pathogenic part played by each of these foreign bodies is discussed, as well as the possibility of the oculoglandular syndrome being due to the reactivation of a latent virus, the organism of cat scratch disease. So far as we know, this work provides the first description of the association of ophthalmia nodosa with the oculoglandular syndrome of Parinaud.